Aqueous film-forming composition for forming antifriction coating film and airbag using same
The aqueous film-forming composition with specific emulsifiers and additives ensures uniform, anti-friction coatings on silicone rubber surfaces, addressing repelling and high-temperature reactivity issues, maintaining coating integrity and performance.
Patent Information
- Application Number
- JP2021528191
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-06-21
- Filing Date
- 2020-06-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-06-12
AI Technical Summary
Existing aqueous coating compositions for silicone rubber surfaces, when applied thinly, often repel and cause coating defects, leading to non-uniform coverage and increased friction, and can react with the base coat at high temperatures, causing deterioration.
An aqueous film-forming composition using an oil-in-water silicone emulsion with specific emulsifiers and a combination of ionic and nonionic emulsifiers, along with a solid lubricant and thickener, to ensure uniform application and adhesion without reacting with the base coat.
The composition achieves uniform, anti-friction coatings without defects, even at thin film thicknesses, and maintains stability at high temperatures, preventing base coat deterioration.
Smart Images

Figure 0007601537000004 
Figure 0007601537000001 
Figure 0007601537000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous film-forming composition which, when applied to a silicone rubber surface, can form a coating film with excellent uniformity without causing repellency or coating defects even when applied in a low application amount and in a thin film with a thickness of 30 μm or less, and which, when applied to the surface of a substrate and moisture is removed, forms a friction-reducing dry coating film that reduces friction and / or blocking on the substrate surface. In particular, the present invention relates to an aqueous film-forming composition suitable for application as a top coat to the silicone rubber surface of airbags and airbag fabrics covered with a base coat of silicone rubber (hereinafter sometimes referred to as "silicone elastomer"), a method for treating a substrate using the same, and a substrate, particularly an airbag, provided with the above-mentioned friction-reducing dry coating film. [Background technology]
[0002] Airbags are generally made from woven or knitted synthetic fibers, such as nylon-6,6 or polyamides such as polyester, and are coated on at least one of their faces with a layer of elastomer. Airbags may be made from flat pieces of fabric that are sewn together after being coated to provide sufficient mechanical strength, or may be woven in one piece with an integrally woven seam. A sewn airbag is generally combined with a coated fabric surface in the airbag interior. A woven airbag in one piece is coated on the outside of the airbag. The preferred elastomers for coating airbags or airbag fabrics are silicone elastomers that are cured organopolysiloxane compositions, especially silicone rubber coatings that are cured by hydrosilylation, i.e., by reaction of alkenyl groups of one polyorganosiloxane with Si-H groups of another silicon-containing material such as a polyorganosiloxane or silane.
[0003] Airbags coated with silicone rubber (silicone elastomer) are described in many published patents and applications, for example, Patent Documents 1-7.
[0004] If an elastomeric base coat is the only coating on the airbag, the surface properties of this base coat can lead to blocking (especially elastomeric coated surfaces sticking to each other during storage at high ambient temperatures and during tight packing of the airbag in the automobile) and very high stresses when the airbag is inflated, which will result in failure of the bag by tearing during inflation or by delamination of the elastomeric base coat from the fabric. Blocking between elastomeric surfaces is also a problem during the manufacture of airbags when elastomer coated fabrics are stored in rolls. Furthermore, many elastomers, such as silicone elastomer coatings, have high surface friction when cured.
[0005] Nos. 5,993,333 and 5,993,352 describe airbag coatings that include at least two separate layers. The first layer (basecoat), which is in contact with the airbag surface, comprises a non-silicone composition made from polyurethane, polyacrylate, polyamide, butyl rubber, hydrogenated nitrile rubber, or ethylene vinyl acetate copolymer. The second layer (topcoat) is a silicone material.
[0006] US Patent No. 5,399,633 describes an airbag coating composition that includes at least two separate and distinct layers. The first layer (base coat), which is in contact with the airbag surface, comprises a silicone elastomer. The second layer (top coat) is preferably a silicone resin.
[0007] US Patent No. 5,399,633 describes an anti-friction silicone varnish for fabrics coated with silicone elastomers. The varnish comprises a crosslinkable silicone composition comprising two silicones which react with each other in the presence of a catalyst allowing crosslinking, and a particulate component comprising a powdered (co)polyamide.
[0008] Furthermore, in Patent Document 11, the applicant has proposed an aqueous coating composition which contains a solid lubricant, a thickener such as a clay mineral, and a binder resin and which is suitable for application as a topcoat to airbags and the like which are coated with a base coat of elastomer or the like, and which forms an anti-friction coating film which reduces friction, etc., and which can form an anti-friction coating film which reduces friction and / or blocking on airbags / airbag fabrics and the like which are coated with silicone elastomer.
[0009] However, these documents contain no description or suggestion whatsoever about an aqueous coating composition that contains a specific combination of emulsifiers, and in particular, that uses a silicone binder consisting of an oil-in-water silicone emulsion that contains a polyorganosiloxane having a high degree of polymerization, to form an antifriction coating film. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] U.S. Patent No. 5,789,084 [Patent Document 2] U.S. Patent No. 5,877,256 [Patent Document 3] U.S. Patent No. 6,709,752 [Patent Document 4] U.S. Patent No. 6,425,600 [Patent Document 5] U.S. Patent No. 6,511,754 [Patent Document 6] International Publication No. 08 / 020605 Brochure [Patent Document 7] International Publication No. 08 / 020635 Brochure [Patent Document 8] U.S. Patent No. 6,177,365 [Patent Document 9] U.S. Patent No. 6,177,366 [Patent Document 10] U.S. Patent No. 7,198,854 [Patent Document 11] JP 2013-516522 A (Japanese Patent No. 5844742) Summary of the Invention [Problem to be solved by the invention]
[0011] Meanwhile, the present applicant has found a new problem with the aqueous coating composition in the above Patent Document 11. In recent years, in the case of airbags and the like that require antifriction coatings, there has been a demand for functional coatings / coating layers on the substrate surface to be applied at a low coating weight, particularly in the form of a thin film of 30 μm or less, in order to reduce weight. However, when an attempt is made to apply a thin layer of the aqueous coating composition (coating agent for topcoat layer) described in Patent Document 11 etc. to the silicone rubber surface, there are cases in which the coating repels, making it impossible to uniformly coat the silicone rubber surface on the substrate.
[0012] The present invention has been made to solve the above-mentioned new problems, and has as its object to provide an aqueous coating-forming composition which, even when applied to a silicone rubber surface in a thickness of 30 μm or less, can uniformly coat the silicone rubber surface without causing repellency or coating defects, and which forms an anti-friction dry coating that reduces friction and / or blocking on the substrate surface.
[0013] The present invention also aims to provide a use of the aqueous film-forming composition, in particular its use for the purpose of forming an antifriction dry coating on a substrate having a silicone rubber surface, which reduces friction or blocking of the substrate surface, and to provide a substrate having the dry coating, in particular an airbag, or a coated fabric which is subsequently formed into an airbag.Furthermore, the present invention aims to provide a surface treatment method which uses the aqueous film-forming composition, and a method for producing an airbag, or a coated fabric which is subsequently formed into an airbag, which includes the surface treatment method.
[0014] On the other hand, the present inventors have found a new problem with respect to the above-mentioned applications. That is, the present inventors have found a new problem that when a silicone rubber-based base coating material is used as a base coating material for an airbag, if an addition reaction type silicone rubber-based top coat is used on the base coating material, the top coat components react with the base coat components in a high-temperature, long-term heat aging test, causing the base coat surface to solidify and become prone to cracking. This problem is difficult to solve with existing addition reaction type silicone rubber-based top coats, and the present invention aims to provide a coated fabric for airbags that has the advantages of a silicone-based top coat, does not cause deterioration of the base coat, and has stable performance even after high temperatures and long periods of time. [Means for solving the problem]
[0015] As a result of intensive research aimed at solving the above problems, the present inventors have found that the above problems can be solved by using an oil-in-water silicone emulsion containing, as a silicone binder, (c1) an ionic emulsifier and (c2) a polyoxyethylene-polyoxypropylene copolymer nonionic emulsifier, in particular, by optimizing the combination of the above emulsifiers and the amount of component (c2) in the dried film and using an oil-in-water silicone emulsion containing a polyorganosiloxane having at least two hydroxyl groups or hydrolyzable groups bonded to highly polymerized silicon atoms per molecule, thereby completing the present invention. Effect of the Invention
[0016] The aqueous coating composition of the present invention, even when applied to a silicone rubber surface in a thickness of 30 μm or less, can uniformly coat the silicone rubber surface without causing repellency or coating defects, and can form a friction-reducing dry coating film that reduces friction and / or blocking of the substrate surface of the surface. This makes it possible to form a uniform antifriction dry coating film on a substrate having a silicone rubber surface even with a small application weight, and to provide a substrate having the dry coating film, particularly an airbag, or a coated fabric that is subsequently formed into an airbag.
[0017] In addition, even when silicone rubber is used as the base coating material, the aqueous coating composition of the present invention does not contain any component that reacts with the base coating material, and therefore does not cause deterioration of the base coat even after high temperatures and long periods of time have passed. Therefore, by using the aqueous coating composition of the present invention, it is possible to provide a coated fabric for airbags that has stable performance over the long term. [Brief description of the drawings]
[0018] [Figure 1] 1 shows photographs of the vicinity of the breakage point of a No. 3 dumbbell after a tensile test when the aqueous coating film-forming composition was combined with a silicone-based base coat material for reference / comparative example / example. In FIG. 1, the left photograph is (untreated, reference experiment), the center photograph is (comparative evaluation example), and the right photograph is (example). BEST MODE FOR CARRYING OUT THEINVENTION
[0019] The aqueous coating film-forming composition of the present invention will be described in detail below. The aqueous coating film-forming composition of the present invention comprises (A) a solid lubricant, (B) (b1) a thickener comprising a water-soluble organic polymer and (b2) a clay mineral, and (C) A silicone-based binder in the form of an oil-in-water silicone emulsion containing (c1) an ionic emulsifier and (c2) a polyoxyethylene-polyoxypropylene copolymer-type nonionic emulsifier. and preferably may further contain additives such as a flame retardant.
[0020] When the entire dried film is taken as 100 mass % by removing water, the aqueous coating film-forming composition contains 40 to 80 mass % of the (A) solid lubricant, 0.50 to 10 mass % of the (B) thickener, 0.60 to 5 mass % of the (c2) polyoxyethylene-polyoxypropylene copolymer type nonionic emulsifier, and 5 to 49.5 mass % of the (C) silicone-based binder (solids), and can form an anti-friction dry coating film that reduces friction and / or blocking on the surface of a substrate.
[0021] Hereinafter, the viscosity of the aqueous film-forming composition of the present invention is measured at 25° C. using a Wells-Brookfield Cone / Plate Viscometer equipped with a 20 mm diameter 2° tapered cone at a shear rate of 1 s (ASTM D4287). Unless otherwise indicated, the viscosities given for all aqueous dispersions of thickeners described herein are measured in the same manner as above.
[0022] [(A) Solid lubricant] The solid lubricant is a component that imparts antifriction properties to the dried coating obtained using the aqueous coating composition of the present invention, which reduces friction and / or blocking, and preferably comprises a phyllosilicate, also known as a layered silicate. Examples of phyllosilicates suitable for use as solid lubricants in the present invention include mica, talc, such as talc microspheres, kaolinite, smectite, sericite and chlorite. The solid lubricant may also or instead comprise a fluoropolymer, such as polytetrafluoroethylene (PTFE), a solid hydrocarbon wax, such as a polyolefin wax. Particularly suitable solid lubricants are (A1) one or more solid lubricants selected from mica, talc, kaolinite, sericite and chlorite.
[0023] The solid lubricant (A) may be present in an amount of at least 1% by weight, or at least 3% by weight, for example, 5 or 10% by weight to a maximum of 40% by weight of the aqueous coating composition including water before the formation of a dry coating film. That is, the content of the component (A) may be in the range of 5 to 40% by weight of the entire aqueous coating composition including water, and is particularly preferably in the range of 10 to 35% by weight, or 15 to 30% by weight.
[0024] From the viewpoint of realizing anti-friction properties in the dried coating film obtained by removing water from the present composition, the content of the (A) solid lubricant is in the range of 40 to 80 mass%, preferably in the range of 45 to 80 mass%, and more preferably in the range of 50 to 80 mass%, when the entire dried coating is taken as 100 mass%.
[0025] [(B) Thickener] The thickener is a component that thickens the aqueous coating film-forming composition of the present invention, improving its coatability, workability, and storage stability, and also functions as a solid component that constitutes a dry film. The thickener of the present invention contains one or more selected from (b1) a water-soluble organic polymer and (b2) a clay mineral, and a thickener formed by premixing these is particularly preferred.
[0026] The thickening performance of the thickener (B) is not particularly limited, but from the viewpoint of the technical effect of the present invention, it is preferable that the thickener has a thickening property such that the viscosity of a 2% by weight aqueous dispersion of the thickener is at least 1000 mPa s at 25°C.
[0027] The water-soluble organic polymer (b1) is a component that can modify the clay mineral (b2) by mixing with the clay mineral, and forms a hydrophilic composite with the clay mineral. In the present invention, only one selected from the water-soluble organic polymer (b1) and the clay mineral (b2) may be used, but it is also possible and preferable to use a mixture of the two.
[0028] Specifically, examples of the component (b1) include water-soluble organic polymers such as polymeric polysaccharides and water-soluble acrylic resins. In particular, the use of a water-soluble organic polymer containing a carboxylate group is preferred, and suitable examples include polyacrylic acids, which are carboxyl-containing addition polymers such as sodium polyacrylate and sodium polymethacrylate.
[0029] (b2) The clay mineral may be natural or synthetic, and examples thereof include natural or synthetic smectite clays such as bentonite, montmorillonite, hectorite, saponite, sauconite, beidellite, and nontronite; and magnesium aluminum silicate. Preferably, the smectite clay is bentonite or montmorillonite. As such smectite clay, for example, Sumecton SA (manufactured by Kunimine Kogyo Co., Ltd.), which is a hydrothermal synthesis product, and Bengel (manufactured by Hojun Co., Ltd.), which is a natural refined product, are available. Note that, as also disclosed in Patent Document 11, these clay minerals may be synthetic smectite clays, which generally have a smaller particle size than natural smectite clays, and for example, the average particle size of synthetic smectite clays is only 5 or 10% of the average particle size of natural smectite. Since synthetic smectite clays have such small particle sizes, a highly viscous aqueous gel composition can be prepared even with a smaller amount of addition than natural smectite clays.
[0030] When imparting heat resistance and flame retardancy to a substrate (e.g., airbag fabric or building material) coated with the aqueous coating film-forming composition of the present invention, the pH of the clay minerals such as smectite clay is preferably within the range of pH 5.0 to 9.0.
[0031] (b2) The clay mineral, for example bentonite or montmorillonite, may be modified by premixing with (b1) the water-soluble organic polymer. For example, the clay mineral and the water-soluble organic polymer may be mixed uniformly in water, and then the mixture may be dried, for example, by spray drying. The resulting dried mixture may be ground to a desired particle size, if necessary, which may be in the range of 1 to 20 μm. The content of the water-soluble polymer in such a mixture may be, for example, in the range of 0.1% by weight to 40% by weight.
[0032] Optionally, (b2) the clay mineral may also be modified by treatment with an alkylalkoxysilane, for example, which may be applied to the clay mineral as neat liquid silane or as a solution in an organic solvent.
[0033] The (B) thickener may be present, for example, in an amount of from 0.1 or 0.2% by weight to 5 or 10% by weight of the coating composition including water etc. prior to the formation of a dry film. Aqueous coating compositions containing 0.5 to 3% thickener are particularly preferred.
[0034] From the viewpoint of uniform application and workability when the present composition containing water is applied thinly to the surface of silicone rubber, the content of the thickener (B) is in the range of 0.50 to 10 mass%, preferably in the range of 2 to 10 mass%, and more preferably in the range of 3 to 9 mass%, assuming the entire dried film to be 100 mass%. If the content of the thickener (B) is less than the lower limit, the uniform application may be insufficient or repellency may occur even if the amount of the component (c2) described below is within the range of the present invention. On the other hand, if the content of the thickener (B) exceeds the upper limit, the viscosity of the composition containing water may become excessively high, which may deteriorate the workability or reduce the durability of the dried film.
[0035] [(C) component] One of the features of the present invention is that the silicone-based binder is in the form of an oil-in-water silicone emulsion containing an ionic emulsifier (c1) and a polyoxyethylene-polyoxypropylene copolymer nonionic emulsifier (c2) as component (C). The aqueous coating composition requires a binder to enhance the adhesion of the solid lubricant (A) to a substrate such as an airbag fabric. A suitable binder is a suitable silicone-based emulsion that hardens to become an elastomer product, but the present inventors have found that by adopting a combination of the above emulsifiers, preferably optimizing the amount used, and using an oil-in-water silicone emulsion containing a polyorganosiloxane having at least two hydroxyl groups or hydrolyzable groups bonded to silicon atoms with a high degree of polymerization as the binder, the silicone rubber surface can be uniformly coated without causing repellency or coating defects even when applied to the silicone rubber surface with a thickness of 30 μm or less.
[0036] [Emulsifier: components (c1) and (c2)] The oil-in-water silicone emulsion, which is the component (C), contains an ionic emulsifier (c1) and a polyoxyethylene-polyoxypropylene copolymer nonionic emulsifier (c2). By using these emulsifiers in combination, the polyorganosiloxane, which is the main component of the component (C), and the alkoxysilane, which is optionally contained, can be stably emulsified in small particle size in the dispersion medium water, and in particular, when the polyorganosiloxane is formed by emulsion polymerization, the emulsion polymerization reaction can be stably advanced to give an oil-in-water silicone emulsion, which is a highly stable emulsion polymerization reaction product. In addition, by using a binder containing a combination of these emulsifiers as the entire aqueous coating film forming composition according to the present invention, the composition can be uniformly applied to the silicone rubber surface in a thin film, and even with a small application weight, a uniform antifriction dry coating film can be formed on a substrate with a silicone rubber surface.
[0037] Here, the (c2) polyoxyethylene-polyoxypropylene copolymer type nonionic emulsifier is an essential component for suppressing the repellency of the coating film and for uniformly covering the silicone rubber surface on the substrate, not just the emulsifier (C), when applying the aqueous coating film-forming composition of the present invention, particularly when applying it thinly to a silicone rubber surface, and if the content of the (c2) component is insufficient, the above technical effects may not be fully achieved. Also, the (c2) component may be added to the aqueous coating film-forming composition of the present invention separately from the emulsifier (C), and this is preferable.
[0038] The ionic emulsifier (c1) may be an anionic surfactant, a cationic surfactant, or an amphoteric surfactant. As the ionic emulsifier, one of these surfactants may be used alone, or two or more different types of surfactants may be used in combination.
[0039] Examples of anionic surfactants include alkylbenzene sulfonates, alkyl ether sulfates, polyoxyethylene alkyl ether sulfates, polyoxyethylene alkyl phenyl ether sulfates, alkyl naphthyl sulfonates, unsaturated aliphatic sulfonates, and hydroxylated aliphatic sulfonates.
[0040] Examples of cationic surfactants include alkyltrimethylammonium salts such as octadecyltrimethylammonium chloride and hexadecyltrimethylammonium chloride; and quaternary ammonium salt surfactants such as dialkyldimethylammonium salts such as dioctadecyldimethylammonium chloride, dihexadecyldimethylammonium chloride and didecyldimethylammonium chloride.
[0041] Examples of amphoteric surfactants include alkylbetaines and alkylimidazolines.
[0042] The component (c2), a polyoxyethylene-polyoxypropylene copolymer nonionic emulsifier, is usually a compound represented by the following general formula (1) or general formula (2). HO(CH2CH2O) a (CH(CH3)CH2O) b (CH2CH2O) C H (1) HO(CH(CH3)CH2O) d (CH2CH2O) e (CH(CH3)CH2O) f H (2) In the general formulas (1) and (2), a, b, c, d, e, and f are the average number of moles of ethylene oxide or propylene oxide added, and are each independently a number from 1 to 350. The weight average molecular weight of the (c2) component is preferably from 1,000 to 18,000, and more preferably from 1,500 to 10,000. When the (c2) component is in a solid state, it can be used in the form of an aqueous solution.
[0043] More specifically, examples of the compound which is component (c2) include the "Pluronic (registered trademark) L" series, "Pluronic (registered trademark) P" series, "Pluronic (registered trademark) F" series, and "Pluronic (registered trademark) TR" series manufactured by ADEKA CORPORATION; Emulgen PP-290 manufactured by Kao Corporation; and Newcol 3240 manufactured by Nippon Nyukazai Co., Ltd., which are available on the market.
[0044] The blending amount of the ionic emulsifier, component (c1), is in the range of 1 to 100 parts by mass, preferably in the range of 1 to 50 parts by mass, and more preferably in the range of 1 to 20 parts by mass, per 100 parts by mass of the polyorganosiloxane, which is the main agent, component (C).
[0045] The blending amount of the (c2) component is in the range of 0.1 to 50 parts by mass, and preferably in the range of 1 to 20 parts by mass, per 100 parts by mass of the polyorganosiloxane which is the main agent of the (C) component.
[0046] The total amount of the (c1) component and the (c2) component is preferably 1 to 30% by mass, more preferably 2 to 20% by mass, of the total amount of the polyorganosiloxane, which is the main component of the (C) component, and the alkoxysilane, etc., which are optionally contained. The ratio of the amount of the (c1) component to the amount of the (c2) component is preferably in the range of 3:1 to 100:1. When the (c2) component is used in combination with the (c1) component to emulsify the polyorganosiloxane, which is the main component of the (C) component, or its precursor component, and other optional components such as alkoxysilane, the particle size of the resulting emulsion particles can be made smaller than that of each component alone, and the stability of the oil-in-water silicone emulsion can be improved.
[0047] The oil-in-water silicone emulsion, component (C), can be prepared by emulsifying and dispersing a cyclic siloxane, a diorganopolysiloxane capped with hydroxyl groups at both molecular chain terminals, an organoalkoxysilane, or the like in water using the emulsifiers of components (c1) and (c2) above, and then, if necessary, adding a catalyst such as an acid or alkaline substance to carry out a polymerization reaction. It is also possible to emulsify and disperse in water a polyorganosiloxane having at least two groups per molecule selected from the group consisting of hydroxyl groups, alkoxy groups, and alkoxyalkoxy groups bonded to silicon atoms, and an aminoxy group-containing organosilicon compound having an average of two aminoxy groups bonded to silicon atoms per molecule using the above emulsifier, and then carrying out a polymerization reaction. This is particularly preferable in that a stable emulsion containing a high-viscosity polyorganosiloxane can be obtained.
[0048] [Polyorganosiloxane in component (C)] The oil-in-water silicone emulsion, component (C), has a structure in which a polyorganosiloxane is emulsified in water in the presence of the above components (c1) and (c2). From the standpoint of function as a silicone binder, the polyorganosiloxane is preferably a polyorganosiloxane having at least two groups per molecule selected from the group consisting of hydroxyl groups, alkoxy groups, and alkoxyalkoxy groups bonded to silicon atoms, and particularly preferably (c3) a polyorganosiloxane having a viscosity at 25°C in the range of 100,000 mPa·s to 20,000,000 mPa·s and having at least two hydroxyl groups or hydrolyzable groups bonded to silicon atoms per molecule.
[0049] The molecular structure of polyorganosiloxane may be linear, cyclic, branched, dendritic, or network-like, but is preferably linear or partially branched. The group selected from the group consisting of hydroxyl, alkoxy, and alkoxyalkoxy groups may be present at the molecular chain terminal, at the molecular chain side chain, or at both. The alkoxy group is preferably an alkoxy group having 1 to 10 carbon atoms, such as a methoxy group, an ethoxy group, an n-propoxy group, an isopropoxy group, an n-butoxy group, a t-butoxy group, a hexyloxy group, a cyclohexyloxy group, an octyloxy group, or a decyloxy group, and the alkoxyalkoxy group is preferably an alkoxyalkoxy group having 2 to 10 carbon atoms, such as a methoxymethoxy group, a methoxyethoxy group, an ethoxymethoxy group, or a methoxypropoxy group.
[0050] Examples of organic groups bonded to silicon atoms other than groups selected from the group consisting of hydroxyl groups, alkoxy groups, and alkoxyalkoxy groups include unsubstituted monovalent hydrocarbon groups and substituted monovalent hydrocarbon groups. From the viewpoint of emulsification-assisting action, the unsubstituted monovalent hydrocarbon group is preferably one having 1 to 10 carbon atoms, more preferably an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an alkenyl group having 2 to 10 carbon atoms, and particularly preferably a methyl group or a phenyl group.
[0051] Examples of the substituted monovalent hydrocarbon group include the above-mentioned unsubstituted monovalent hydrocarbon groups, particularly groups in which some or all of the hydrogen atoms of an alkyl group or phenyl group having 1 to 10 carbon atoms have been substituted with a substituent such as a halogen atom such as fluorine or chlorine; an epoxy functional group; a methacryl functional group; an acrylic functional group; an amino functional group; a sulfur-containing functional group; an alkoxy group; a hydroxycarbonyl group; or an alkoxycarbonyl group.
[0052] From the standpoint of the strength of the cured coating obtained by removing water from the oil-in-water silicone emulsion of the present invention, adhesion to the substrate, and reduction in surface tack and friction of the cured coating, the viscosity of the polyorganosiloxane at 25°C is preferably in the range of 100,000 mPa·s to 20,000,000 mPa·s, more preferably in the range of 300,000 mPa·s to 10,000,000 mPa·s, even more preferably in the range of 500,000 mPa·s to 5,000,000 mPa·s, and most preferably in the range of 750,000 mPa·s to 3,500,000 mPa·s. If the viscosity of the polyorganosiloxane is less than the lower limit, the strength of the cured film obtained by removing water from the oil-in-water silicone emulsion and its adhesion to the substrate may be insufficient, and the surface of the cured film may become sticky, and the dried coating film containing the (A) solid lubricant may not be able to achieve a smooth surface. On the other hand, if the viscosity of the polyorganosiloxane exceeds the upper limit, it is difficult to emulsify it.
[0053] Such polyorganosiloxane is preferably a diorganopolysiloxane having hydroxyl groups blocked at both molecular chain terminals, and is represented by the general formula: HO(R 1 2SiO) m An example of the polyorganosiloxane is represented by the formula: 1 is the same as the unsubstituted or substituted monovalent hydrocarbon group bonded to a silicon atom other than a hydroxyl group or a hydrolyzable group described above. m is an integer of 2 or more, and is preferably a number that results in the viscosity at 25°C in the above-mentioned viscosity range of 100,000 mPa s to 20,000,000 mPa s.
[0054] There are no particular limitations on the method for producing such polyorganosiloxane, and polyorganopolysiloxanes obtained by known methods such as equilibrium polymerization may be emulsified in water with an emulsifier such as component (c1) described below. From the standpoint of handling during production and particle size and stability during emulsion dispersion, however, organopolysiloxanes obtained by emulsion polymerization using organopolysiloxanes with a lower degree of polymerization, which are precursors of polyorganosiloxanes, are preferably used.
[0055] Particularly preferred is a polyorganosiloxane obtained by emulsion polymerization of polyorganosiloxane precursors (c3a) a polyorganosiloxane having at least two hydroxyl groups or hydrolyzable groups bonded to silicon atoms per molecule and (c3b) an aminoxy group-containing organosilicon compound having an average of two aminoxy groups bonded to silicon atoms per molecule in the presence of the above-mentioned components (c1) and (c2).
[0056] The precursor (c3a) polyorganosiloxane having at least two hydroxyl groups or hydrolyzable groups bonded to silicon atoms in each molecule is a raw material component constituting the above polyorganosiloxane, and is preferably a linear polyorganosiloxane having a lower viscosity and having hydroxyl groups or hydrolyzable groups bonded to silicon atoms at both ends of the molecular chain. More specifically, component (c3a) is a diorganopolysiloxane capped with hydroxyl groups at both molecular chain ends and having a viscosity at 25°C of 100,000 mPa·s or less, preferably in the range of 50 to 50,000 mPa·s, and most preferably HO(R 1 2SiO) n H, and n is a number that gives the viscosity of component (a) at 25°C in the above-mentioned viscosity range, preferably in the range of 50 to 50,000 mPa s. 1 is the same as the unsubstituted or substituted monovalent hydrocarbon group bonded to a silicon atom other than a hydroxyl group or a hydrolyzable group described above, and is particularly preferably a methyl group or a phenyl group.
[0057] (c3b) Aminoxy group-containing organosilicon compounds having an average of two aminoxy groups bonded to silicon atoms per molecule are components that promote the formation of a cured coating that has good surface hardness and rubber-like elasticity without a tacky feel by reacting and crosslinking components (c3a) together.
[0058] Component (c3b) contains an average of two aminoxy groups bonded to silicon atoms per molecule, and the aminoxy groups may be present only on the side chains of the molecular chain, or only on both ends of the molecular chain, or an average of one each on both the end and the side chain of the molecular chain. If component (c3b) contains an average of three or more aminoxy groups per molecule, gelation of the mixture is likely to occur inside the emulsification equipment during emulsification or in the pre-mixing step before emulsification, and the gel may adhere to the production equipment and the elongation of the resulting cured coating may be poor.
[0059] Examples of such aminoxy group-containing organosilicon compounds include polydiorganosiloxanes capped with aminoxy groups at both molecular chain terminals, diorganosiloxane-organoaminooxysiloxane copolymers capped with aminoxy groups at one molecular chain terminal, diorganosiloxane-organoaminooxysiloxane copolymers capped with triorganosilyl groups at both molecular chain terminals, cyclic diorganosiloxane-organoaminooxysiloxane copolymers, and diaminooxydiorganosilanes. Among these, polydiorganosiloxanes capped with aminoxy groups at both molecular chain terminals are preferred. The amount of component (c3b) is 0.1 to 100 parts by mass, preferably 0.5 to 50 parts by mass, and more preferably 1 to 20 parts by mass, per 100 parts by mass of component (c3a).
[0060] The component (c3b) preferably has the general formula: R 2 R 1 2SiO(R 1 R 3 SiO) n (R 1 2SiO) p SiR 1 2R 2 In the above formula, R 1 is the same as above, and among them, an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, or an alkenyl group having 2 to 10 carbon atoms is preferable, and a methyl group or a phenyl group is particularly preferable. 3 is an aminoxy group. When n is 0, R 2 is an aminoxy group; when n is 1, R 2 One of the R 2 is a group selected from the group consisting of unsubstituted monovalent hydrocarbon groups having 1 to 10 carbon atoms, halogen-substituted monovalent hydrocarbon groups having 1 to 10 carbon atoms, hydroxyl groups, alkoxy groups having 1 to 10 carbon atoms, and alkoxyalkoxy groups having 2 to 10 carbon atoms; when n is 2, R 2 is a group selected from the group consisting of unsubstituted monovalent hydrocarbon groups having 1 to 10 carbon atoms, halogen-substituted monovalent hydrocarbon groups having 1 to 10 carbon atoms, hydroxyl groups, alkoxy groups having 1 to 10 carbon atoms, and alkoxyalkoxy groups having 2 to 10 carbon atoms.
[0061] Examples of the unsubstituted monovalent hydrocarbon include the same groups as those mentioned above, and a methyl group or a phenyl group is preferable. Examples of the halogen-substituted monovalent hydrocarbon group include the unsubstituted monovalent hydrocarbon group in which some or all of the hydrogen atoms are substituted with halogen atoms, and a halogen-substituted alkyl group such as a chloromethyl group, a 3,3,3-trifluoropropyl group, a 3,3,4,4,5,5,5-heptafluoropentyl group, or a difluoromonochloropropyl group is preferable. Examples of the alkoxy group and the alkoxyalkoxy group include the same groups as those mentioned above.
[0062] The aminoxy group is -ON(R 4 ) 2 and groups represented by the following formulas: [ka] R in the formula 4 is a linear or branched alkyl group having 1 to 5 carbon atoms. 5is a divalent hydrocarbon group having 2 to 15 carbon atoms or a divalent organic group having a molecular chain main chain consisting of 3 to 17 carbon atoms and 1 to 3 nitrogen atoms or 1 to 2 oxygen atoms, and examples thereof include -(CH2)2-, -(CH2)5-, -(CH2)6-, -(CH2)7-, -(CH2)2-O-(CH2)2-, -(CH=CH)-(CH=CH)-, -(CH=N)-(CH=CH)-, and -(C6H4)-(CH2)2-. Among these, -(CH2)6- and -(CH2)2-O-(CH2)2- are preferred. Among these, a dialkylaminoxy group in which an alkyl group having 1 to 5 carbon atoms is bonded to a nitrogen atom is preferable, and preferable examples of the aminoxy group include a dimethylaminoxy group, a diethylaminoxy group, a dipropylaminoxy group, a dibutylaminoxy group, a diheptylaminoxy group, an ethylmethylaminoxy group, a propylmethylaminoxy group, a propylethylaminoxy group, a butylmethylaminoxy group, a butylethylaminoxy group, a butylpropylaminoxy group, a heptylmethylaminoxy group, a heptylethylaminoxy group, a heptylpropylaminoxy group, and a heptylbutylaminoxy group, and a diethylaminoxy group is preferable.
[0063] In the above formula, n is 0, 1 or 2, preferably 0 or 2, and more preferably 0. When n is 0, R 2 is an aminoxy group, and when n is 1, R 2 At least one of the above formulas is an aminoxy group. 2 is preferably an aminoxy group from the viewpoint of availability.
[0064] In the formula, p is an integer of 0 or more, and there is no particular upper limit for p, but in terms of ease of emulsification, p is preferably an integer in the range of 0 to 1000, more preferably an integer in the range of 2 to 200, and most preferably an integer in the range of 4 to 140.
[0065] Examples of such aminoxy group-containing organosilicon compounds include those represented by the following formula: In the formula, Me represents a methyl group, Et represents an ethyl group, and Pr represents a propyl group. (Et2NO)Me2SiOSiMe2(ONEt2) (Et2NO)Me2SiO(Me2SiO) 12 SiMe2(ONEt2) (Et2NO)Me2SiO(Me2SiO) 40 SiMe2(ONEt2) (Et2NO)Me2SiO(Me2SiO) 80 SiMe2(ONEt2) Me2Si(ONEt2)2 Me3SiO(MeSi(ONEt2)O)2SiMe3 Me3SiO(Me2SiO)4(MeSi(ONEt2)O)2SiMe3 Me3SiO(Me2SiO) 15 (MeSi(ONEt2)O)2SiMe3 Me3SiO(Me2SiO)3(MeSi(ONEt2)O)7SiMe3
[0066] Furthermore, if component (c3b) remains in the oil-in-water silicone emulsion, it is a component that contributes to the reaction and crosslinking between the polyorganosiloxane in the silicone binder and the colloidal silica component that is optionally added, and is capable of forming a cured coating that has good surface hardness and rubber-like elasticity without a sticky feel.
[0067] [Colloidal silica in component (C)] Component (C) of the present invention may and preferably further contains (c4) colloidal silica. Colloidal silica is a component for improving the strength of a cured coating based on a silicone binder and its adhesion to a substrate, and by containing a relatively large amount of colloidal silica, calculated as solids, relative to component (A) in the oil-in-water emulsion that is component (C) of the present invention, this component is capable of forming a cured coating that has little surface adhesion (tack) and is smooth and has excellent friction reducing properties on the surface of the substrate.
[0068] Colloidal silica is available as an aqueous dispersion in which 5 to 40% by mass of silica particles are colloidally dispersed in water, has many silanol groups on the surface, and generally has a particle diameter of about 1 nm to 1 μm. Such colloidal silica is preferably a basic aqueous dispersion stabilized by sodium ions or ammonium ions. The pH of colloidal silica as a basic aqueous dispersion is preferably 7.0 or more, more preferably more than 9.0. The shape of the silica fine particles of colloidal silica is not particularly limited, and is generally spherical, but elongated or pearl necklace-shaped ones may also be used.
[0069] In the present invention, the amount of colloidal silica (c4) in component (C) must be in the range of 5 to 120 parts by mass, calculated as solids content, per 100 parts by mass of polyorganosiloxane (c3) having a viscosity at 25°C in the range of 100,000 mPa s to 20,000,000 mPa s and having at least two hydroxyl groups or hydrolyzable groups bonded to silicon atoms per molecule, preferably in the range of 10 to 110 parts by mass, and particularly preferably in the range of 20 to 100 parts by mass.
[0070] Here, the solid content of colloidal silica refers to the non-volatile silica particle content, and when the amount of colloidal silica is within the above range, it is possible to impart good smoothness to the surface of the cured film obtained by removing water from the oil-in-water silicone emulsion composition of the present invention and consisting mainly of polyorganosiloxane or its crosslinked reaction product. On the other hand, if the amount of colloidal silica is too small or too large, the surface of the cured film may become tacky or crack.
[0071] When the polyorganosiloxane in the (C) component is obtained by emulsion polymerization, the (c4) colloidal silica can be added during or after polymerization. Specifically, an aqueous dispersion of colloidal silica particles containing water may be added to an emulsion containing polyorganosiloxane, or an aqueous dispersion of colloidal silica particles may be added to an emulsion containing the (c3a) component, which is a precursor of the polyorganosiloxane, the (c3) component, to proceed with the emulsion polymerization reaction.
[0072] Examples of such colloidal silica include Snowtex 20, Snowtex 30, etc. manufactured by Nissan Chemical Industries, Ltd.; Adelite AT-20, etc. manufactured by Asahi Denka Kogyo Co., Ltd.; Crebosol 30R9, etc. manufactured by Clariant Japan K.K.; Ludox (trademark) HS-40, etc. manufactured by DuPont; Cataloid S-20L, etc. manufactured by Catalysts and Chemicals Industry Co., Ltd.; and Silicadol-20 manufactured by Nippon Chemical Industry Co., Ltd.
[0073] The component (C) is an oil-in-water emulsion and contains water. The amount of water may be sufficient to maintain a stable aqueous emulsion state, and is not particularly limited. However, the amount of water derived from the aqueous dispersion of colloidal silica and independent water is generally in the range of 5 to 95 mass% of the entire composition, which is the component (C). When excluding water in the aqueous dispersion of colloidal silica, the amount of water is preferably in the range of 0 to 500 mass parts, preferably 10 to 200 mass parts, per 100 mass parts of the polyorganosiloxane (c3) having a viscosity at 25°C in the range of 100,000 mPa·s to 20,000,000 mPa·s and having at least two hydroxyl groups or hydrolyzable groups bonded to silicon atoms in one molecule.
[0074] The oil-in-water silicone emulsion composition, which is component (C), may further contain (c5) a compound represented by the general formula R 1 a Six 4-aor a partial hydrolysis condensate of the alkoxysilane or alkoxyalkoxysilane. In the formula, R is the same as above, and is preferably a methyl group or a phenyl group. X is an alkoxy group having 1 to 10 carbon atoms or an alkoxyalkoxy group having 2 to 10 carbon atoms, and examples thereof include the same groups as above. a is 0, 1 or 2, with 0 or 1 being preferred. In particular, the component (c5) is preferably a tetraalkoxysilane, an alkyltrialkoxysilane, a tetraalkoxyalkoxysilane, or an alkyltrialkoxyalkoxysilane.
[0075] The component (c5) may be a partial hydrolysis condensate of the above-mentioned organoalkoxysilane, organoalkoxyalkoxysilane, tetraalkoxysilane, or tetraalkoxyalkoxysilane.
[0076] From the standpoint of improving the strength of the cured film and adhesion to the substrate, the (c5) component is preferably blended in an amount of 0.1 to 50 parts by weight, and more preferably 1 to 15 parts by weight, per 100 parts by weight of the (c3) component. If the blend amount of the (c5) component is less than 0.1 part by weight per 100 parts by weight of the (c3) component, the strength of the cured film obtained by removing water from the aqueous silicone emulsion composition produced may not be sufficiently improved, while if the blend amount exceeds 50 parts by weight, the amount of alcohol produced as a by-product increases, which may have adverse effects on the environment and human body and may change the formability of the cured film over time, which is not preferred.
[0077] The oil-in-water silicone emulsion composition (C) is preferably formulated with an amine compound (c6) as a pH adjuster. Diethylamine is a preferred amine compound. Since these components (c6) also function as a curing catalyst (described below) when removing moisture, they can promote the condensation reaction of each component, and in particular, can achieve curing reactivity free of heavy metals such as tin.
[0078] The blend amount of component (c6) as a pH adjuster is preferably within the range of 0.01 to 5 mass %, and more preferably 0.1 to 2 mass %, of the total mass of component (C).
[0079] [Other optional ingredients] The oil-in-water silicone emulsion composition, which is component (C), can contain other components as necessary, such as pigments, antifoaming agents, penetrating agents, antistatic agents, inorganic powders, preservatives, rust inhibitors, silane coupling agents other than component (c5) such as bis(trimethoxysilylpropyl)disulfide, pH adjusters other than component (c6), buffers, ultraviolet absorbers, curing catalysts, water-soluble resins, organic resin emulsions, pigments, dyes, and the like.
[0080] The average particle size (average primary particle size) of the silicone emulsion particles in the oil-in-water silicone emulsion composition, which is component (C), may be in the range of 50 to 600 nm, preferably 300 nm or less, and particularly preferably 250 nm or less, from the viewpoints of storage stability, formability of a cured film, and stability when diluted with water. The average particle size of the emulsion particles can be measured by a dynamic light scattering method or the like.
[0081] [Amount of (c2) polyoxyethylene-polyoxypropylene copolymer nonionic emulsifier in the dried film] As described above, the (c2) component not only functions as an emulsifier for the silicone binder (C), but also, by including a certain amount or more in the aqueous coating film-forming composition, when the aqueous coating film-forming composition according to the present invention is applied to the surface of a silicone rubber, particularly in a film thickness of 30 μm or less, it can suppress repellency and coating defects and provide an effect of uniformly covering the surface of the silicone rubber. Specifically, the content of the (c2) component is in the range of 0.6 to 5 mass%, preferably in the range of 0.6 to 4 mass%, and more preferably in the range of 0.6 to 3.5 mass%, assuming that the entire dried film is 100 mass%. If the content of the (c2) component is less than the lower limit, repellency and coating defects may occur when the aqueous coating film-forming composition is thinly applied to the surface of the silicone rubber. Note that this effect depends on the amount of the (c2) component, so if there is a shortage, the above technical effect may not be achieved even if a nonionic emulsifier other than the (c2) component is added.
[0082] The amount of the emulsifier in the component (C) may be adjusted so as to satisfy the above range, or the component (c2) may be added to the aqueous coating film-forming composition of the present invention separately from the component (C). In particular, by adopting a preparation method in which the component (c2) is blended with the composition of the present invention separately from the component (C), there is an advantage in that the desired content of the component (c2) can be achieved without impairing the stability of the component (C).
[0083] [Silicone binder content in dried film] The content of the silicone-based binder in the form of (C) oil-in-water silicone emulsion can be selected as desired, but is preferably in the range of 5 to 49.5% by mass, and more preferably in the range of 10 to 45% by mass, when the entire dry film is taken as 100% by mass. If the amount of the (C) component exceeds the upper limit, the blending amounts of the (A) and (B) components in particular become relatively small, and the object of the present invention of forming an antifriction dry coating film that reduces friction and / or blocking on the substrate surface may not be achieved. On the other hand, if the amount of the (C) component is too small, the amount of the binder becomes insufficient, and even if the content of the (c2) component satisfies the above range, it may cause repellency or coating failure, particularly when applied to a silicone rubber surface with a film thickness of 30 μm or less, and the silicone rubber surface may not be uniformly coated.
[0084] [Curing catalyst] The aqueous coating film forming composition of the present invention or the binder (C) component may contain a curing catalyst. In the present invention, the incorporation of a curing catalyst is optional, but it can be incorporated in order to quickly crosslink and cure the components of the composition of the present invention through a condensation reaction. Specific examples of the curing catalyst include organic tin compounds such as dibutyltin dilaurate, dibutyltin diacetate, tin octenate, dibutyltin dioctate, tin laurate, dioctyltin diversatate, dioctyltin diacetate, and dibutyltin bisoleyl maleate; tetrabutyl titanate, tetrapropyl titanate, and dibutoxybis(ethylacetoacetate)titanium; organic titanium compounds such as dimethylformamide; acidic compounds such as hydrochloric acid, sulfuric acid, and dodecylbenzenesulfonic acid; alkaline compounds such as ammonia and sodium hydroxide; amine compounds such as n-hexylamine, guanidine, 1,8-diazabicyclo[5.4.0]undecene (DBU), and 1,4-diazabicyclo[2.2.2]octane (DABCO); organic zirconium esters such as zirconium tetrapropylate and zirconium tetrabutylate; zirconium tributoxyacetylacetonate zirconium-based condensation promoters such as oxozirconium compounds such as zirconium bis(2-ethylhexanoate) oxide and zirconium acetylacetonate (2-ethylhexanoate) oxide; aluminum alcoholates such as aluminum triethylate, aluminum triisopropylate and aluminum tri(sec-butylate); aluminum chelate compounds such as diisopropoxyaluminum(ethylacetoacetate), aluminum tris(ethylacetoacetate) and aluminum tris(acetylacetonate); aluminum-based condensation promoters such as aluminum acyloxy compounds such as hydroxyaluminum bis(2-ethylhexanoate); and condensation reaction catalysts such as organic acid metal salts such as zinc stearate, zinc octylate, zinc acetate and iron octylate. Except when the curing catalyst is water-soluble, it is preferable to prepare the curing catalyst in advance in the form of an emulsion by emulsifying and dispersing the catalyst in water using a surfactant.Furthermore, the amine compounds (c6) that can be used in the component (C) also function as curing catalysts. By using these compounds, it is possible to design compositions that do not contain curing catalysts that contain metals such as tin, which is preferable from the standpoint of reducing the environmental impact.
[0085] The amount of the condensation reaction catalyst used in the aqueous film-forming composition of the present invention is not particularly limited, and can be any amount within the range in which the purpose of condensation reaction promotion is achieved. However, the use of the condensation reaction catalyst is optional, and it may not be used in the present composition. In addition, a composition containing a condensation reaction catalyst is described in U.S. Pat. No. 4,221,688, the contents of which are incorporated herein by reference. The binder may also be made from a siloxane-based polymer and a suitable self-catalyzing crosslinker, a surfactant, and water. This type of composition is described, for example, in U.S. Pat. No. 5,994,459, the contents of which are incorporated herein by reference.
[0086] [Flame retardant] The aqueous film-forming composition of the present invention may further contain a flame retardant since it is suitable for use in airbag coating. For example, the composition of the present invention is suitable for airbag coating because it forms a lubricating dry coating that reduces friction and / or blocking on the substrate surface, but it is important that airbags are not easily ignited and do not support combustion by their nature, and airbags generally require the addition of a flame retardant to pass the stringent flammability tests that may be applied to airbags. When the topcoat of the present invention is applied to an airbag coated with silicone rubber, there is generally no problem with flammability, but when a topcoat that does not contain a flame retardant is applied to an airbag coated with an organic resin, it may not pass a flammability test such as the US Federal Motor Vehicles Safety Standards Test FMVSS#302 (hereinafter referred to as "FMVSS#302"), and the addition of a flame retardant is practically important.
[0087] In particular, the composition according to the present invention is suitable for use as a coating agent for use in the top coat of an airbag or a covering fabric which is subsequently formed into an airbag, and the effect of the flame retardant is often most effective when present in the top coat. An example of a preferred flame retardant is aluminum trihydrate, preferably not surface-treated. Flame retardants also include other metal hydroxides such as magnesium hydroxide, metal oxides such as ferrite oxides and titanium oxide, carbonates such as zinc carbonate, and carbon black. The content of these flame retardant components may be in the range of 2 to 40% by mass, preferably 5 to 25% by mass, based on the total composition, and a component at least partly consisting of aluminum trihydrate may be selected as the flame retardant, and is preferred.
[0088] [Other optional ingredients] The aqueous coating film-forming composition of the present invention may optionally contain other components, as necessary, such as pigments, defoamers, penetrating agents, dyes, antistatic agents, surfactants, preservatives, adhesion promoters, rust inhibitors, pH adjusters, buffers, UV absorbers, curing catalysts, water-soluble resins, and / or deodorants, such as zeolite and / or activated carbon.
[0089] [Total viscosity of composition and viscosity measurement method] From the viewpoint of uniform application and workability, the aqueous coating composition of the present invention preferably has a viscosity of 1000 mPa·s or more. The viscosity is measured at 25°C at a shear rate of 1 s-1 using a Wells-Brookfield Cone / Plate Viscometer equipped with a 20 mm diameter 2° tapered cone (ASTM D4287). Unless otherwise indicated, the viscosity described in this specification is measured by the same method as above.
[0090] [Application method and application target] The aqueous film-forming composition of the present invention may be applied to a substrate by various techniques. Different materials may require different coating methods. For example, the coating may be applied as a topcoat to the coated airbag or coated airbag fabric by roller application, curtain coating, spraying, or knife-over-roll. Roller application is often preferred as an effective method to achieve uniform coating at low coat weights. The amount of coating composition transferred to the fabric is a function of the pressure on the roller and / or the depth of the etched surface during gravure. The topcoat is preferably applied at a coat weight of 10 g / m2 up to 100 g / m2 on a wet weight basis. A coat weight of 1 g / m2 or more after drying can provide the necessary low coefficient of friction and prevent blocking.
[0091] The amount of aqueous diluent (water and any co-solvents mixed with water) in the aqueous coating composition of the present invention may be controlled depending on the viscosity required for coating and the required coating weight. Typically, the coating composition has a solids content of 1.5-50% by weight and contains 98.5-50% aqueous diluent.
[0092] The aqueous film-forming composition of the present invention can generally be applied to any substrate where reduced friction and / or reduced blocking is required.The coating composition is particularly effective when applied as a topcoat on airbags or other similar applications such as emergency chutes for aircraft and hot air balloons, but can also be used in other applications such as keypads, mold forming, coating wires, and to improve handling in molding processes such as silicone molding processes.
[0093] When the aqueous film-forming composition of the present invention is applied as a topcoat to a coated airbag or coated airbag fabric, the basecoat may be any of the known silicone rubber-based or organic resin-based cured products, and is not particularly limited.From the viewpoint of airbag coating, the basecoat is particularly preferably an organopolysiloxane composition, which preferably contains an organopolysiloxane having an aliphatic unsaturated hydrocarbon or hydrocarbonoxy substituent, an organosilicon crosslinker having at least three silicon-bonded hydrogen atoms, a catalyst capable of promoting the reaction of the aliphatic unsaturated hydrocarbon or hydrocarbonoxy substituent with a Si-H group, and a reinforcing filler.Such a basecoat forms a silicone rubber layer upon curing, which has high flexibility and is effective in sealing the airbag, but has a high coefficient of friction.
[0094] The aqueous coating film-forming composition of the present invention has the advantage that, when applied to the surface of silicone rubber, even when applied in a low coating amount and in a thin film thickness of 30 g / m2 or less, it can form a coating film with excellent uniformity without causing repellency or coating defects, and therefore has the advantage that, for a substrate with the above-mentioned silicone rubber as an undercoat, a lubricating dry coating film that reduces friction and / or blocking can be formed on the surface by applying only a small amount while maintaining excellent flame retardancy. Therefore, by using the aqueous coating film-forming composition of the present invention and surface treatment with it, it is possible to obtain an airbag that is lightweight and has excellent flame retardancy and lubrication properties, or a covering fabric that is then formed into an airbag.
[0095] Furthermore, the aqueous coating composition of the present invention has an advantage for substrates that use the above-mentioned silicone rubber as a base coat. That is, even when silicone rubber is used as a base coating material, the aqueous coating composition of the present invention does not contain any component that reacts with the base coating material, so it does not cause deterioration of the base coat even after high temperatures and long periods of time (for example, harsh heat resistance conditions such as 107°C for 408 hours). Therefore, by using the aqueous coating composition of the present invention, it is possible to provide a coated fabric for airbags that has stable performance over the long term.
[0096] If the basecoat is curable, it is typically cured before applying the topcoat, but in an alternative method, the aqueous film-forming composition of the present invention may be applied to an uncured basecoat to reduce friction and / or blocking, and the combination of the basecoat composition and the coating composition to reduce friction and / or blocking may be heat cured.
[0097] If the coating to reduce friction and / or blocking is applied to a cured basecoat, the coating to reduce friction and / or blocking can be cured at ambient temperature or can be cured more quickly at elevated temperatures, for example in the range of 50-200° C., especially 100-150° C. One possible method of curing at elevated temperatures involves applying the coating composition to a heated substrate, for example a coated airbag or airbag fabric immediately after heat curing the basecoat.
[0098] The coatings of the present invention provide a low friction surface on the substrate to which they are applied, and when applied over a coating having a high coefficient of friction, the coatings of the present invention reduce friction on the coated airbag surface, thus reducing wear on the airbag which can reduce pressure retention of the airbag when subjected to movement during vehicle use.
[0099] The coating of the present invention also prevents the coated fabric surfaces from blocking, i.e., sticking together during storage or tight packing in the airbag compartment of a vehicle, which can cause very high stresses when the airbag inflates, resulting in failure of the bag by tearing or by delamination of the silicone undercoat from the fabric.
[0100] The invention is illustrated by the following examples in which parts and percentages are by weight unless otherwise indicated. EXAMPLES
[0101] These examples and comparative examples use a modified clay mineral thickener MCT1 containing bentonite and sodium polyacrylate, which is formed by homogeneously mixing bentonite with an aqueous solution of sodium polyacrylate, drying the mixture, and then grinding it. MCT1 contains a mixture of sodium carbonate and polyacrylate at a content of about 15%. A 1.5% aqueous solution of MCT1 has a viscosity of 20,000 mPa·s, which was measured at 25°C at a shear rate of 1 s-1 using a Wells-Brookfield cone / plate viscometer equipped with a 2° tapered cone with a diameter of 20 mm (ASTM D4287).
[0102] The present invention will be described in detail below with reference to examples and comparative examples. In the examples, the viscosity is a value measured at 25°C, the parts expressing the blend amount mean parts by mass, and the % expressing the content means % by mass. In the formulas, Me represents a methyl group, and Et represents an ethyl group. The contents of each component of the present invention in the dry film, when the entire dry film is taken as 100% by mass, are also shown in the tables.
[0103] The silicone rubber-coated nylon fabric used for evaluation was a nylon fabric with a weave density of 46 x 46 threads, on which silicone rubber (DOW, addition reaction type airbag coating material LCF3760A&B) with a hardness (JIS type A) of 10 degrees was applied at 100 g / m2 using a knife coater.
[0104] [Evaluation of cured film and coatability] The oil-in-water silicone emulsion composition (film-forming composition) of each experimental example was applied to the surface of a silicone rubber-coated nylon airbag fabric with a bar coater, with the wet weight being 30 g / m2 or 15 g / m2, and the applicability was evaluated. Furthermore, each coating amount was thermally cured at 140°C, and the following items were evaluated. The coating amount was adjusted by changing the number of the bar coater. Viscosity: Measured using a rheometer AR500 manufactured by TA Instruments. Uniformity: Evaluated visually. Blocking test: Two pieces of coated fabric cut to a size of 50 x 50 mm were prepared, and placed one on top of the other with the coating surfaces facing each other. A cylindrical iron weight with a diameter of 75 mm and a weight of 1.0 kg was placed on top of the pieces and left in an oven at 150°C for 24 hours. After removing from the oven, one end of the piece was fixed and the other end was pulled with a push-pull gauge. If it peeled off with a force of less than 50g, it was considered to have passed the test.
[0105] [Evaluation of physical properties in combination with silicone-based base coat materials] Rubber properties: A 1mm thick rubber sheet was made by curing silicone rubber with a hardness (JIS type A) of 10 degrees for 5 minutes in a mold and a press at 150°C. A topcoat agent was applied to one side of the sheet to a coating weight of 12g / m2, and the sheet was heated in a 150°C oven for 30 seconds to cure. A heat aging test was then carried out in a 107°C oven for 408 hours. The specimens were removed from the heat aging test and allowed to stand at room temperature for one day, after which hardness and tensile tests were carried out using a JIS No. 3 dumbbell.
[0106] [Example 1] (a) 92.5 parts of a polydimethylsiloxane with hydroxydimethylsiloxy groups blocked at both ends of the molecular chain and a viscosity of 2,400 mPa·s, (b) 7.5 parts of an aminoxy group-containing polysiloxane represented by the formula (1): Et2NO(Me2SiO)7NEt2, (C2) 3.75 parts of a polyoxyethylene-polyoxypropylene copolymer-type nonionic emulsifier (manufactured by Adeka, product name Pluronic (registered trademark) F108) that had been mixed and homogenized in advance, (C1) a dispersion of 12.5 parts of a 40% aqueous solution of sodium alkanesulfonate, and emulsified with an emulsifier. (D) 86 parts of water, (B-1) 44.0 parts of colloidal silica (manufactured by Nissan Chemical, product name Snowtex 30, active ingredient 30%, pH 10, colloidal silica with the surface stabilized by sodium), and (G) 1.25 parts of diethylamine were added to the resulting emulsion and mixed homogenously. Further, 2.5 parts of (F) methyltriethoxysilane was added and mixed uniformly, and the mixture was allowed to stand at room temperature for 2 weeks to prepare an oil-in-water silicone emulsion base.
[0107] The viscosity of organopolysiloxane (A) obtained by emulsion polymerization after reaction was measured by the following procedure. (a) 92.5 parts of a polydimethylsiloxane with a viscosity of 2,400 mPa·s and terminated at both ends of the molecular chain with hydroxydimethylsiloxy groups, (b) 7.5 parts of an aminoxy group-containing polysiloxane represented by formula (1): Et2NO(Me2SiO)7NEt2, were mixed uniformly with (C2) 7.5 parts of a polyoxyethylene-polyoxypropylene copolymer type nonionic emulsifier (manufactured by ADEKA, product name Pluronic (registered trademark) F108) that had been mixed and homogenized in advance, and (C1) a dispersion of 12.5 parts of a 40% aqueous solution of sodium alkanesulfonate, and emulsified using an emulsifier. After leaving to stand for one week, 10 g of the prepared emulsion was added with stirring to 10 g of isopropyl alcohol, and only the precipitated dimethylsiloxane was dried at 105°C for 3 hours and measured using a Brookfield type viscometer. The viscosity at 25°C was 1,800,000 mPas.
[0108] 100 parts of the obtained oil-in-water silicone emulsion base were uniformly mixed with 73.54 parts of (B-2) colloidal silica and 0.5 parts of additional emulsifier component (c2) product name Pluronic (registered trademark) F108 to obtain silicone emulsion No.1.
[0109] (E) 73 parts of a 1.5% anionic polymer composite refined bentonite (product name: Bengel W100U: Hojun Co., Ltd.) aqueous solution and 15 parts of talc powder were mixed into a dispersion, and 12 parts of the silicone emulsion (No. 1) obtained above was uniformly mixed to obtain an oil-in-water silicone emulsion composition (=coating composition) of the present invention.
[0110] The resulting oil-in-water silicone emulsion was left at 25°C for six months, after which no separation was observed and the dispersion was stable. Furthermore, when evaluated using the method described above, it was found to be capable of forming a cured film. The evaluation results are shown in Table 1.
[0111] [Example / Evaluation of physical properties of topcoat agent for comparative evaluation in combination with silicone-based basecoat material] The oil-in-water silicone emulsion of Example 1 was used as a topcoat agent by the above-mentioned method, and the effect on the physical properties of silicone rubber was confirmed when it was combined with a silicone-based base coat material. On the other hand, an addition reaction type silicone rubber-based topcoat agent (product name DC3715BASE / CURING AGENT, manufactured by DOW) was used instead of the oil-in-water silicone emulsion of Example 1, and the effect on the physical properties of silicone rubber was compared when it was combined with a silicone-based base coat material by the above-mentioned method. As a reference experiment, an untreated rubber sheet with a thickness of 1 mm was prepared without applying a topcoat agent by the above-mentioned method.
[0112] The evaluation results are shown in Table 2 and Figure 1. Here, Figure 1 shows photographs of samples after a heat aging test in a 107°C oven for 408 hours, including a left photograph (untreated, reference experiment), a center photograph (comparative evaluation example), and a right photograph (Example 1).
[0113] [Example 2] Except for changing the amount of additional emulsifier component (product name: Pluronic (registered trademark) F108) to 1.5 parts, a silicone emulsion (No. 2) and a coating composition were prepared in the same manner as in Example 1, and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0114] [Comparative Example 1] A silicone emulsion (No. 3) and a coating composition were prepared in the same manner as in Example 1, except that no additional emulsifier component was added, and evaluations were carried out in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0115] [Comparative Example 2] Except for changing the additional emulsifier component to 1.0 part of a nonionic emulsifier mainly composed of C10 Guerbet alcohol ethoxylate (BASF product name LUTENSOL (registered trademark) XP30), a silicone emulsion (No. 4) and a coating composition were prepared and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0116] [Comparative Example 3] Except for changing the additional emulsifier component to 1.0 part of a viscosity modifier (Primal ASE60, manufactured by Rohm and Haas Co., Ltd.), a silicone emulsion (No. 5) and a coating composition were prepared and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.
[0117] [Table 1] *Systems that contain nonionic emulsifiers other than (C2) **System with added viscosity modifier [Table 2]
[0118] [Summary] The aqueous coating film-forming compositions (=coating film compositions) of Examples 1 and 2 satisfied the constitution of the present invention, had a coatable viscosity, and could be uniformly applied onto silicone rubber whether the application amount was 30 g / m2 or a thinner application amount of 15 g / m2. They were capable of forming a thin, lightweight, and uniform dried coating film that did not cause blocking between coatings.
[0119] In contrast, in Comparative Examples 1 to 3, the amount of component (c2) was insufficient, and when applied at a coating amount of 30 g / m2, repellency was more likely to occur than in the Examples, and particularly when applied at a thin coating amount of 15 g / m2, repellency occurred on the silicone rubber, making it impossible to form a coating film with sufficient uniformity. For this reason, it was difficult to apply the compositions of Comparative Examples 1 and 2 thinly, particularly to silicone rubber, to obtain a coating film with excellent functionality. Furthermore, when a viscosity modifier was added instead of component (c2), it was not possible to apply the composition uniformly on the silicone rubber, even when applied at a coating amount of 30 g / m2.
[0120] As a result of evaluating the effect on the silicone rubber-based base coat material, as shown in Table 2, the currently used addition reaction type silicone rubber-based top coat agent (comparative evaluation example) had a smaller elongation of 790%, compared to the elongation of the untreated silicone rubber, which was 1060%. On the other hand, when the aqueous coating film-forming composition (=coating film composition) of Example 1 was used as the top coat agent, no reduction in elongation was observed. Furthermore, as a result of observing the vicinity of the breakage point of the dumbbell after the tensile test, fine cracks were generated on the surface only in the center photo (comparative evaluation example) of the rubber treated with the addition reaction type silicone rubber-based top coat agent, unlike the left photo (untreated, reference experiment) and the right photo (Example 1). This is presumed to be because the crosslinking agent component contained in the addition reaction type silicone rubber-based top coat agent solidified the surface of the silicone-based base coat by reaction. On the other hand, in the top coat agent of Example 1 of the present invention, no reaction occurs with the silicone-based base coat material and no deterioration of the base coat material occurs, so it is presumed that no cracks are generated, similar to the untreated one.
[0121] [Evaluation test example using a woven fabric (a fabric bag with a base coat made of silicone rubber)] A hollow weave fabric was produced by coating both sides with silicone rubber that cures by addition reaction and has a hardness (JIS type A) of 10 degrees to an application weight of 60 g / m2, and then heating for 2 minutes at 180°C to cure (reference experiment), the silicone rubber-coated hollow weave fabric being made of 470 decitex nylon 66 with a warp density of 46 threads / inch and a weft density of 46 threads / inch, with a bag-shaped internal space of 5 liters in the center and this internal space equipped with a gas inlet. The silicone rubber-coated hollow weave fabric corresponds to a base fabric bag having a base coat made of silicone rubber.
[0122] After producing a silicone rubber-coated hollow weave fabric in the same manner as above, a topcoat agent is applied on top of it so that the coating weight is 12 g / m2, and then heated in a 150°C oven for 30 seconds to harden and produce a silicone rubber-coated hollow weave fabric. After that, a heat aging test is carried out in a 107°C oven for 408 hours, and after leaving it at room temperature for one day, gas at a pressure of 125 kPa is blown into the internal space of the hollow weave fabric through the gas blowing port to set the pressure in the internal space to 70 kPa. The gas blowing port is immediately closed, and the rate at which the pressure in the internal space decreases is measured.
[0123] With currently used addition reaction type silicone rubber based top coat agents, the rate of pressure drop is significantly greater than that of bags coated with only untreated silicone rubber, but when treated with the aqueous coating film forming composition (=coating film composition) of Example 1 as a top coat agent, the rate of pressure drop in the internal space is equivalent to that of a bag coated with only silicone rubber as in the reference experiment, and there is no problem of reduced reliability due to deterioration or cracks in the base fabric provided with a base coat made of silicone rubber that hardens by addition reaction. [Industrial Applicability]
[0124] The aqueous coating film-forming composition of the present invention, when applied to or impregnated into a substrate and then the water is removed, forms a dry coating film with antifriction properties that has rubber-like elasticity and reduces friction and / or blocking on the surface of the substrate. Therefore, it is useful as a paper coating agent used in water-based paints and inks, thermal paper and inkjet paper, etc., a release agent for molds and rubber, a resin coating agent used in automobile weather strips, gaskets, rubber hoses, etc., a fiber treatment agent used in clothing and airbags, a release agent, cosmetics, building materials, etc. Furthermore, when the aqueous coating forming composition of the present invention is used on an airbag that has been surface-treated with silicone rubber, since it does not react with the base coat, it is possible to maintain the flexibility of the silicone base coat even when the airbag is left in an environment at high temperatures for a long period of time, and the performance of the airbag can be maintained for a long period of time even in such an environment.
Claims
1. (A) a solid lubricant which is talc; (B) a thickener comprising a premix of (b1) sodium polyacrylate and (b2) bentonite, the component (b1) being in the range of 0.1 to 40 mass % of the total mass of the component (B); and (C) A silicone-based binder in the form of an oil-in-water silicone emulsion comprising (c1) an ionic emulsifier, (c2) a polyoxyethylene-polyoxypropylene copolymer type nonionic emulsifier, and (c3) a polyorganosiloxane having a viscosity at 25°C in the range of 100,000 mPa·s to 20,000,000 mPa·s and having at least two hydroxyl groups or hydrolyzable groups bonded to silicon atoms in each molecule, and further comprising (c4) 20 to 100 parts by mass of colloidal silica (converted into solid content) per 100 parts by mass of component (c3), the average primary particle size of the emulsion particles being in the range of 50 to 600 nm. By removing water, When the entire dry coating is taken as 100% by mass, 40 to 80 mass % of the (A) solid lubricant; 0.50 to 10 mass % of the thickener (B); The silicone-based binder (C) is contained in an amount of 10 to 49.5 mass % (solid content), and The dry coating contains 0.60 to 0.97 mass % of the polyoxyethylene-polyoxypropylene copolymer nonionic emulsifier (c2), An aqueous film-forming composition that forms a lubricating dry coating that reduces friction and / or blocking on a substrate surface.
2. The aqueous coating film-forming composition according to claim 1, wherein component (A) accounts for 5 to 40 mass% of the total composition including water.
3. 2. The aqueous coating film-forming composition according to claim 1, wherein component (c3) is a polyorganosiloxane obtained by emulsion polymerization of (c3a) a polyorganosiloxane having at least two hydroxyl groups or hydrolyzable groups bonded to silicon atoms per molecule, and (c3b) an aminoxy group-containing organosilicon compound having an average of two aminoxy groups bonded to silicon atoms per molecule, in the presence of component (c1) and component (c2).
4. 4. The aqueous film-forming composition according to claim 1, which is used for the purpose of forming an antifriction dry coating film on a silicone rubber surface which reduces friction or blocking.
5. 5. The aqueous film-forming composition according to claim 1, which is a coating for an airbag or for a covering fabric which is formed into an airbag.
6. 6. Use of the aqueous film-forming composition according to any one of claims 1 to 5 for forming an antifriction dry coating on a substrate having a silicone rubber surface, the antifriction dry coating reducing friction or blocking of the substrate surface.
7. A substrate having a lubricating dry coating film which reduces friction or blocking on the substrate surface, the coating film being obtained by removing water from the aqueous coating film-forming composition according to any one of claims 1 to 5.
8. 8. The substrate of claim 7, wherein said dry coating comprises a structure overcoated onto a silicone rubber surface.
9. 9. The substrate of claim 7 or claim 8, wherein the substrate is an airbag or a covered fabric that is subsequently formed into an airbag.
10. 6. An airbag having a structure in which a silicone rubber surface on a substrate is covered with a dry coating film obtained by removing water from the aqueous coating film-forming composition according to any one of claims 1 to 5.
Citation Information
Patent Citations
Semiconductor integrated circuit device
JP1983044742A
Oil-in-water silicone emulsion composition
JP2010235931A
Anti-friction coating
JP2013516522A
Liquid silicone rubber coating composition
US5789084A
Liquid silicone rubber coating composition for application to air bags
US5877256A
